The Luxury Culture in Arab Film: Route 10 by Omar Naim (A Semiotic Analysis of Roland Barthes) - Syifa Nur Afiffah; Edi Komarudin; Yadi Mardiansyah (Hasanuddin University, 2025)
This study examines the representation of luxury culture in Omar Naim’s film Route 10 using Roland Barthes’ semiotic approach. The research aims to reveal how luxury objects and fashion function not merely as literal signs but as symbols of social hierarchy, prestige, and cultural adaptation. Employing a qualitative descriptive method with content analysis, selected dialogues and scenes are analyzed to uncover denotative and connotative meanings embedded in both narrative and visual elements. The findings indicate that luxury is depicted through icons such as branded cars, high-heeled shoes, and premium bags, representing elite status and global prestige. Indexes, including personal assistants, palatial residences, and exclusive privileges, highlight social hierarchies and structural inequalities. Symbols, such as formal attire, wedding gowns, and the fusion of religious tradition with modernity, reflect both aspirational and contradictory aspects of elite culture, including elitism, hypocrisy, and social distinction. Overall, the film presents luxury as a phenomenon that functions both as a marker of prestige and a source of social tension, illustrating how material and symbolic representations of wealth influence perceptions of identity, status, and cultural values in contemporary Arab society.